Automated data and video processing in track cycling - Vleeschouwers, T.; Decorte, R.; Slembrouck, M.; Verstockt, S. (Journal of Science and Cycling, 2025)
Recent advances in sports data analytics have driven the development of integrated performance monitoring systems. This abstract describes the implementation and uses cases of integrating a pan-tilt-zoom (PTZ) camera into the existing Wireless Cycling Network (WCN) deployed at the Wielercentrum Eddy Merckx in Gent, Belgium. WCN combines a precise timing system, ANT+ sensor data collection and an anaerobic capacity (W`) estimation. Automated PTZ camera tracking and recording enables immediate visual analysis by coaches. AI-computer vision models are used for detection and qualitative analysis of team pursuit changeovers. In addition to elite use cases, general engagement can be improved with event-specific real-time data display and personalized videos and session reports. These integrated capabilities and the modular design streamline coaching workflows and provide a platform for future applications across various track-based sports. Future work includes further development of analysis tools to support coaches, production deployment of the complete system and implementing it at additional tracks.